Immune responses during COVID-19 infection - Cléa Melenotte; Aymeric Silvin; Anne-Gaëlle Goubet; Imran Lahmar; Agathe Dubuisson; Alimuddin Zumla; Didier Raoult; Mansouria Merad; Bertrand Gachot; Clémence Hénon; Eric Solary; Michaela Fontenay; et al. (OncoImmunology, 2020)
Over the past 16 years, three coronaviruses (CoVs), severe acute respiratory syndrome CoV (SARS-CoV) in 2002, Middle East respiratory syndrome CoV (MERS-CoV) in 2012 and 2015, and SARS-CoV-2 in 2020, have been causing severe and fatal human epidemics. The unpredictability of coronavirus disease-19 (COVID-19) poses a major burden on health care and economic systems across the world. This is caused by the paucity of in-depth knowledge of the risk factors for severe COVID-19, insufficient diagnostic tools for the detection of SARS-CoV-2, as well as the absence of specific and effective drug treatments. While protective humoral and cellular immune responses are usually mounted against these betacoronaviruses, immune responses to SARS-CoV2 sometimes derail towards inflammatory tissue damage, leading to rapid admissions to intensive care units. The lack of knowledge on mechanisms that tilt the balance between these two opposite outcomes poses major threats to many ongoing clinical trials dealing with immunostimulatory or immunoregulatory therapeutics. This review will discuss innate and cognate immune responses underlying protective or deleterious immune reactions against these pathogenic coronaviruses.